The Neurology of Consciousness: Cognitive Neuroscience and Neuropathology edited by Steven Laureys and Giulio Tononi - Kelly, Edward F. (Journal of Scientific Exploration, 2012)
This information-packed volume, without doubt a landmark event in the developing neuroscientific study of consciousness, deserves the attention of anyone interested in this subject. It is a sequel and companion to an earlier collection, The Boundaries of Consciousness: Neurobiology and Neuropathology, also edited by Steven Laureys (2005), which contains the proceedings of a 2004 conference sponsored by the Association for the Scientific Study of Consciousness (ASSC). Published initially as a special issue of Progress in Brain Research (volume 150), Boundaries has been reissued in paperback and appears on the ASSC website as one of its official titles. Both volumes include many prominent figures in contemporary neuroscience, and the two volumes together constitute about as clear, comprehensive, and authoritative a picture as one can find anywhere of the current state of mainstream neuroscientific thinking about consciousness and the brain. Like classical physics of the late 19th century, it is a picture of great power and beauty; nevertheless, just as discordant phenomena such as black-body radiation and the photoelectric effect presaged the rise of quantum mechanics, this book, precisely because of its clarity, reveals signs of trouble ahead.